Obesity of mice lacking VAP-1/SSAO by Aoc3 gene deletion is reproduced in mice expressing a mutated vascular adhesion protein-1 (VAP-1) devoid of amine oxidase activity - Valentin Jargaud; Sandy Bour; François Tercé; Xavier Collet; Philippe Valet; Anne Bouloumié; Jean-Claude Guillemot; Pascale Mauriège; Sirpa Jalkanen; Craig Stolen; Marko Salmi; David J. Smith; et al. (Journal of Physiology and Biochemistry, 2021)

Insects and incest: Sib‐mating tolerance in natural populations of a parasitoid wasp - Marie Collet; Isabelle Amat; Sandrine Sauzet; Alexandra Auguste; Xavier Fauvergue; Laurence Mouton; Emmanuel Desouhant (Molecular Ecology, 2020)
Sib‐mating avoidance is a pervasive behaviour that is expected to evolve in species subject to inbreeding depression. Although laboratory studies provide elegant demonstrations, small‐scaled bioassays minimize the costs of mate finding and choice, and thus may produce spurious findings. We therefore combined laboratory experiments with field observations to examine the existence of inbreeding avoidance using the parasitoid wasp Venturia canescens . In the laboratory, our approach consisted of mate‐choice experiments to assess kin discrimination in population cages with competitive interactions. A higher mating probability after sib rejections suggested that females could discriminate their sibs; however, in contrast to previous findings, sib‐mating avoidance was not observed. To compare our laboratory results to field data, we captured 241 individuals from two populations. Females laid eggs in the lab, and 226 daughters were obtained. All individuals were genotyped at 18 microsatellite loci, which allowed inference of the genotype of each female's mate and subsequently the relatedness within each mating pair. We found that the observed rate of sib‐mating did not differ from the probability that sibs encountered one another at random in the field, which is consistent with an absence of sib‐mating avoidance. In addition, we detected a weak but significant male‐biased dispersal, which could reduce encounters between sibs. We also found weak fitness costs associated with sib‐mating. As such, the sex‐biased dispersal that we found is probably sufficient to mitigate these costs. These results imply that kin discrimination has probably evolved for purposes other than mate choice, such as superparasitism avoidance.

Lipid rafts: dream or reality for cholesterol transporters? - Stéphane Orlowski; Christine Coméra; François Tercé; Xavier Collet (European Biophysics Journal, 2007)